Determining species identity from confiscated pangolin remains using DNA barcoding. Issue 1 (1st January 2016) - Luczon, Adrian U.; Ong, Perry S.; Quilang, Jonas P.; Fontanilla, Ian Kendrich C.
Abstract: Illegal wildlife trade is one of the key threats to biodiversity. A requisite in combating illegal wildlife trade is through effective and efficient identification of confiscated wildlife or wildlife remains. This can be done through DNA barcoding. In this study, DNA barcoding was employed on several cases of poaching in the Philippines involving 85 unidentified pangolin remains. Of these, 73 specimens confiscated from Palawan were identified as the Palawan endemic Manis culionensis, but no deep divergences were observed, suggesting that the samples originated from a single locality. The other 12 individuals, which were part of a large haul of pangolin carcasses recovered from a foreign fishing vessel that ran aground in Tubattaha Reefs, Philippines, were identified as the Malayan Pangolin, M. javanica . They split into two groups with 3.3% mean genetic distance, suggesting at least two geographic origins.